Modeling of the self trapping of helium and the trap mutation in tungsten using DFT and empirical potentials based on DFT. Issue 20 (29th October 2014) - Boisse, J.; De Backer, A.; Domain, C.; Becquart, C.S.
Abstract: Abstract : Density functional theory calculations and molecular dynamics with a recently developed potential for W–He were used to evaluate the thermal stability of helium-vacancy clusters ( n He .m v) as well as pure interstitial helium clusters in tungsten. The stability of such objects results from a competitive process between thermal emission of vacancies, self interstitial atoms (SIAs), and helium, depending on the helium-to-vacancy ratio in mixed clusters or helium number in pure interstitial helium clusters. We investigated in particular the ground state configurations as well as the activation barriers of self trapping and trap mutation, i.e., the emission of one SIA along with the creation of one vacancy from a vacancy-helium or pure helium object.